Cerebral Sinovenous Thrombosis in a Child with Idiopathic Nephrotic Syndrome - L. Ghedira Besbes; S. Haddad; A. Gabsi; M. Hassine; Ch. Ben Meriem; M. N. Guediche (Case Reports in Nephrology)
Nephrotic syndrome (NS) is a renal disorder characterized by heavy proteinuria, hypoalbuninemia, edema and hypercholesterolemia. Nephrotic syndrome in children is known to be associated with an hypercoagulable state and thromboembolic complications. However cerebral sinovenous thrombosis (CSVT) is very rare. Here we report a seven-year-old child with steroid-dependent idopathic nephrotic syndrome resulting from a minimal change disease, developed multiple cerebral sinovenous thrombosis, presenting with headache, left sixth nerve palsy, and papilledema. The diagnosis of CSVT was established by cranial computed tomography, magnetic resonance imaging, and magnetic resonance angiography. He gradually recovered after anticoagulant therapy. CSVT is very rare in nephrotic children. The diagnosis of CSVT should be considered in any patient with nephrotic syndrome who develops neurologic symptoms. This report highlights the importance of suspecting and recognizing this potentially life threatening complication and initiating early treatment.